FACTORS RELATED TO ABORTUS EVENTS IN MITRA MEDIKA RSU TANJUNG MULIA MEDAN IN 2019 - qori armiza septia; Asriwati Amirah; Jitasari Tarigan Sibero (HUMAN CARE JOURNAL, 2020)
Abortion is an important problem in public health because it affects maternal morbidity and mortality. Based on data from the World Health Organization (WHO) in 2016, around 830 women die from pregnancy-related complications worldwide every day. During 2010-2014, an estimated 56 million abortions occur each year worldwide. The aim is to find out factors related to the abortion at Mitra Medika Tanjung Mulia Medan Hospital in 2019.         This research uses a Mix Methods research with a Sequential Explanatory strategy. The approach used in quantitative retrospectives and qualitative uses a case study approach. The population in this study were all pregnant women who experienced abortion recorded in the medical records of Mitra Medika Hospital Tanjung Mulia Medan as many as 73 respondents. The sample in a quantitative approach of 73 respondents with the technique of Total Population while for qualitative 2 pregnant women who have abortion, 2 husbands, 1 midwife. Data collection is carried out with primary, secondary and tertiary data. Data analysis was performed by univariate, bivariate analysis. Qualitative data analysis with data reduction, data presentation, and drawing conclusions.         Data obtained from the results of statistical tests show there is a relationship between age and abortion p value 0.005, there is a relationship of work with abortion p value 0.017, there is a relationship of parity with abortion p value 0.022, there is a relationship between historical abortion with abortion p value 0.001. And there is no correlation between contraceptive failure and abortion p value 0.297. Qualitatively based on in-depth interviews with informants that the cause of the occurrence of abortion is due to the age of the mother at risk, a history of previous abortion and fatigue at work. Another factor related to the incidence of abortion is husband's support.         The conclusion of this study is that there is a relationship between age, occupation, parity, history of abortion of pregnant women with abortion and there is no relationship between contraceptive failure of pregnant women with abortion in Mitra Medika Tanjung Mulia Hospital in 2019. It is expected that health workers can improve the quality of services in efforts to manage abortion and providing information about pre-conception preparation and health monitoring during pregnancy.